Construction of a river buffalo (Bubalus bubalis) whole-genome radiation hybrid panel and preliminary RH mapping of chromosomes 3 and 10 - Amaral, M. E. J.; Owens, K. E.; Elliott, J. S.; Fickey, C.; Schaeffer, A. A.; Agarwala, R.; Womack, J. E. (Blackwell Publishing, 2007)
The buffalo (Bubalus bubalis) is a source of milk and meat, and also serves as a draft animal. In this study, a 5000-rad whole-genome radiation hybrid (RH) panel for river buffalo was constructed and used to build preliminary RH maps for BBU3 and BBU10 chromosomes. The preliminary maps contain 66 markers, including coding genes, cattle expressed sequence tags (ESTs) and microsatellite loci. The RH maps presented here are the starting point for mapping additional loci that will allow detailed comparative maps between buffalo, cattle and other species whose genomes may be mapped in the future. A large quantity of DNA has been prepared from the cell lines forming the river buffalo RH panel and will be made publicly available to the international community both for the study of chromosome evolution and for the improvement of traits important to the role of buffalo in animal agriculture.
Keywords: Gene mapping; Radiation hybrid panel; River buffalo; Whole genome